OPTIMIZATION OF GOVERNMENT EXPENDITURES STRUCTURE IN CONDITIONS OF IMPLEMENTATION OF SOCIAL AND ECONOMIC REFORMS IN UKRAINE - Dekhtyar Nadezhda Anatolevn; Deyneka Olga Valerevna; Pihul Nataliya Georgievna (Scientific Journal of Pedagogy and Economics, 2019)
The article considers the concept of the optimal distribution of government expenditures. It also proves the fact that the structure of budget expenditures is determined by such factors as: the socioeconomic structure of the country, the level of economic development, the established property relations, the specifics of the historical path of the country and the mentality of the population. The types and groups of public expenditures were systematized on the basis of theoretical studies, namely: government expenditures spent to perform general national functions of the state and to provide its security support; government expenditures spent to support the entrepreneurial activity of the state; government expenditures spent to perform education and social functions. Also there was made an analysis of the composition and the structure of the state expenditures of the European Union and Ukraine. The article considers the reasons of ineffective planning and use of expenditures of the Ukrainian budget. There has been established a priority of the government expenditures in the way of realization of the tasks of financial policy. It has been also determined that the priority of government expenditures in the EU and Ukraine coincide, but there are, anyway, some divergences in some shares of their expenditures. According to that, there has been proposed an optimization model of the structure of government expenditures of the Ukrainian budget. The proposed structure of government expenditures, which is being carried out in Ukraine at the present stage, meets the common European requirements and is aimed at realization of socio-economic reforms.